2001
DOI: 10.1002/jcu.1043
|View full text |Cite
|
Sign up to set email alerts
|

Transabdominal sonography of the normal gastroesophageal junction in children

Abstract: Our results indicate that visualization of the gastroesophageal junction and measurement of the abdominal esophagus are readily achievable with real-time sonography in healthy children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 15 publications
1
26
0
Order By: Relevance
“…However, visualization of the thoracic esophagus using transthoracic sonography is limited by the sternum, ribs, vertebrae, and lungs. Some previous studies 3,5 indicated that a short lower portion of the thoracic esophagus could be demonstrated by transabdominal sonography through the window of the left lobe of the liver. But visualization of the majority of the thoracic esophagus has been considered difficult and even impossible.…”
Section: Received 25 November 2003; Accepted 13 April 2004mentioning
confidence: 99%
See 1 more Smart Citation
“…However, visualization of the thoracic esophagus using transthoracic sonography is limited by the sternum, ribs, vertebrae, and lungs. Some previous studies 3,5 indicated that a short lower portion of the thoracic esophagus could be demonstrated by transabdominal sonography through the window of the left lobe of the liver. But visualization of the majority of the thoracic esophagus has been considered difficult and even impossible.…”
Section: Received 25 November 2003; Accepted 13 April 2004mentioning
confidence: 99%
“…The mean demonstrable length of the thoracic esophagus was 10.2 ± 1.9 cm and the mean thickness 3.2 ± 0.3 mm. Keywords: esophagus; thoracic esophagus; ultrasonography C onventional sonography has been used widely, in both children and adults, for the noninvasive evaluation of the abdominal [1][2][3][4][5] and cervical 6-9 esophagus. However, visualization of the thoracic esophagus using transthoracic sonography is limited by the sternum, ribs, vertebrae, and lungs.…”
Section: Received 25 November 2003; Accepted 13 April 2004mentioning
confidence: 99%
“…However, children do not tolerate barium x-ray studies well, and endoscopy is an invasive method. 1,2 Most of the sonographic studies in children with diseases of the esophagus use high-resolution endoscopic sonography, which has been found to be a useful imaging technique for evaluation of the thickness of the esophageal wall and mucosal and submucosal lesions and the extent of lesions involving the deeper structures of the esophagus in congenital esophageal stenosis, corrosive esophagitis, esophageal atresia, eosinophilic esophagitis, and gastroesophageal reflux. [3][4][5][6][7] However, endoscopic sonography is an invasive method for assessing the esophageal wall.…”
Section: Discussionmentioning
confidence: 99%
“…The cervical esophagus can be sonographically evaluated, considering its lateral location in relation to the trachea, and because of its proximity to the surface and interposition of soft tissue such as the left thyroid lobe (12) . In healthy individuals, the intra-abdominal segment of the esophagus is easily accessible by ultrasonography because of its posterior positioning in relation to the left hepatic lobe acting as an access window for ultrasound imaging (a relatively homogeneous organ that displaces the bowel loops with gas) (13)(14)(15) . In the present study, the method demonstrated that there was no statistically significant difference between ETTs with water and yogurt and between genders, which was not observed with the individuals in dorsal decubitus (10) , although a possible cause could be the individuals positioning (orthostasis).…”
Section: Discussionmentioning
confidence: 99%